Strategi Pemanfaatan Media Sosial Anggota Legislatif Muda Pada Pemilu 2024 - Zumiraj, M. Alam Zumiraj (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2025)
This study aims to examine the social media usage strategies used by young legislators in winning the 2024 election. This study is a qualitative study that aims to understand the phenomenon of political communication used by legislative candidates in the 2024 Election based on social media. As well as knowing the supporting factors and inhibiting factors of social media usage in the 2024 election. The approach used in this study is a case study, namely the researcher will select several legislative candidates who actively use social media as part of their campaign strategy. Based on the research that has been done, it can be concluded that the 2024 Election is an arena for competing social media utilization strategies between legislative candidates. The findings in this study are that elected legislative members have strategies in utilizing social media. These strategies are: forming a media team, choosing the right content target, choosing the type of content to be displayed, choosing the most comfortable social media application for legislative members, choosing the right upload time, collaborating with more famous people, and mixing modern strategies with traditional ones. The supporting factors found are ease of use, a solid digital media team, and media that can be used for free. Inhibiting factors are the political practice of dawn raids as well as network and human resource problems. Keywords: Media, Social, Politics, Legislative